The Problem of Animal Pain - Dougherty, T. author. aut Link
XIII, 197 p.
Keywords: Animal suffering constitutes perhaps the greatest challenge to rational belief in the existence of God. Considerations that render human suffering theologically intelligible seem inapplicable to animal suffering. In this book, Dougherty defends radical possibilities for animal afterlife that allow a soul-making theodicy to apply to their case.